2017
DOI: 10.1111/padm.12342
|View full text |Cite
|
Sign up to set email alerts
|

Yours emotionally: How emotional intelligence infuses public service motivation and affects the job outcomes of public personnel

Abstract: We investigate the role of emotions in the public sector and their relation with work outcomes typical of public arenas. We focus on the emotional intelligence of public healthcare staff and its potential impact on public service motivation, job satisfaction, affective commitment and the quality of service to citizens. Using data from 200 nurses in a large Israeli public hospital, we examine a mixed model of direct and indirect relationships. The findings support direct positive relationships between emotional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(67 citation statements)
references
References 76 publications
2
55
0
2
Order By: Relevance
“…Our findings provide preliminary support for the idea that civil servants' EI may enhance their public sector engagement. The findings are in line with existing public administration literature on the significant role of emotions in the outcomes of public administration personnel (e.g., Guy and Lee ; Levitats and Vigoda‐Gadot ). This prominent role of emotions is underscored by the finding of the moderating effect of managers' EI on the relationship between their subordinates' EI and PSE.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our findings provide preliminary support for the idea that civil servants' EI may enhance their public sector engagement. The findings are in line with existing public administration literature on the significant role of emotions in the outcomes of public administration personnel (e.g., Guy and Lee ; Levitats and Vigoda‐Gadot ). This prominent role of emotions is underscored by the finding of the moderating effect of managers' EI on the relationship between their subordinates' EI and PSE.…”
Section: Discussionsupporting
confidence: 90%
“…Since Berman and West's () work, EI has been found to be positively related to work‐related constructs such as job satisfaction (Vigoda‐Gadot and Meisler ), affective commitment, public service motivation and service quality (Levitats and Vigoda‐Gadot ), and well‐being (Brunetto et al ). The latter study also confirmed the positive relationship between EI and work engagement among employees in the public sector.…”
Section: Theory and Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…This was one of the few studies that proved the mediating role of self-motivation between the predictors that include emotional intelligence and social skills and the dependent variable that is cultural adjustment of expatriates. Past studies have pointed out that emotional intelligence is related to self-motivation [66]. Scholars have also revealed that social skills are another component of emotional intelligence.…”
Section: Discussion and Recommendationmentioning
confidence: 99%
“…A study by Palmer et al [38] found that EI was correlated with the inspiration motivation component of transformational leadership. A study by Levitats an Vigoda-Gadot [66] found a positive relationship between EI and employees" motivation and job outcomes. Social skills are another component of emotional intelligence and socially skilled people tend to have knack for finding rapport [34].…”
Section: The Mediating Role Of Self-motivationmentioning
confidence: 98%